Assessment of Methemoglobin, Hemoglobin, Ferritin and Lactate dehydrogenase in COVID-19 Patients - Vaishali S. Pawar; Divya Anand Jain; Ajit Sontakke; Vivek Redkar; Satyajeet Pawar (Journal of Pure and Applied Microbiology, 2022)
Today world is trying to cope with the biggest pandemic caused by Coronavirus disease 2019 (COVID-19). The disease is graded as mild, moderate, serious and critical illness. Very few studies are done with methemoglobin along with other parameters for the assessment of the severity of COVID-19 disease. The objectives of the study were to estimate methemoglobin (Met-Hb), hemoglobin (Hb), ferritin and lactate dehydrogenase (LDH) levels in patients with COVID-19 disease and to investigate the interaction between these parameters and the severity of the disease. This observational study was conducted in three groups of COVID-19 patients- moderate, severe and critical, each group containing 30 patients, between June 2021 and September 2021 in the biochemistry department of a tertiary care hospital. For all patients, Met-Hb, Hb, ferritin, and LDH levels were estimated on the 2nd-3rd day of hospital admission. Patients in the critical group were older and had significantly high values of Met-Hb, ferritin and LDH and significantly low values of Hb (P<0.05). In multivariate ordinal regression analysis, older age (OR-3.08; 95%CI:1.19-7.19;P-0.019), higher values of LDH (OR-8.66; 95%CI:2.53-29.5; P-0.001) and ferritin (OR-3.08; 95%CI:1.09-8.7;P-0.033) were independently associated with severity of the disease. A cut-off value of 410.50 U/L for LDH predicted the severity of the disease with 90% sensitivity and 88.3% specificity. In conclusion, higher levels of LDH and ferritin were related to the severity of the disease in COVID-19 cases. Although Met-Hb showed a minimal increase without any association with severity, it may be an underlying cause of hypoxia that may go unnoticed. So, monitoring of all these parameters should be done at intervals.